2020
DOI: 10.1177/1077559520932665
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse and Risk of Revictimization: Impact of Child Demographics, Sexual Abuse Characteristics, and Psychiatric Disorders

Abstract: Approximately half of child sexual abuse (CSA) victims report sexual revictimization later in life; however, there is limited rigorous evidence concerning factors contributing to sexual and nonsexual forms of revictimization. This article investigates the relationships between CSA and a range of revictimization experiences. It also examines the role of other individual-level factors (demographics, CSA characteristics, psychiatric disorders) in the risk of revictimization. The study compares data from a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 71 publications
4
27
0
4
Order By: Relevance
“…These ndings stress the need to move away from what is currently considered traumatic within the diagnostic classi cations systems and adopt a wider and more ideographic understanding of what constitutes a traumatic experience. While there is extensive quantitative evidence on the potential links between trauma and psychosis, including re-victimisation [45], our ndings indicate that the views of people with psychosis are sometimes, although not always, congruent with these research ndings. Consistently with studies that found that revictimization increases the likelihood of having psychotic experiences [46], our results suggest that feeling constantly scared as a consequence of trauma, or feeling continuously on the edge of a mental breakdown, led participants to a point where they were so worn down that they could not cope with anything anymore.…”
Section: Discussionsupporting
confidence: 43%
“…These ndings stress the need to move away from what is currently considered traumatic within the diagnostic classi cations systems and adopt a wider and more ideographic understanding of what constitutes a traumatic experience. While there is extensive quantitative evidence on the potential links between trauma and psychosis, including re-victimisation [45], our ndings indicate that the views of people with psychosis are sometimes, although not always, congruent with these research ndings. Consistently with studies that found that revictimization increases the likelihood of having psychotic experiences [46], our results suggest that feeling constantly scared as a consequence of trauma, or feeling continuously on the edge of a mental breakdown, led participants to a point where they were so worn down that they could not cope with anything anymore.…”
Section: Discussionsupporting
confidence: 43%
“…In a study that analyzed the recurrence of reported cases of violence, it was possible to note that there was a recurrence of sexual violence or negligence, even after previous reports of physical and sexual violence, suggesting that in some cases reporting is not enough to change the victim's environment may not prevent revictimization [40]. A systematic review revealed that, revictimization is associated with greater suffering, presence of psychiatric disorders, di culty in interpersonal relationships and coping, self-blame, shame, and revictimization in adult life [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…For the data analyses, STATA 13.0 (StataCorp, LLC, USA) was used to conduct descriptive statistics analysis, MLR, and QR analysis. Descriptive statistics were used to analyze the participants' age, gender, marital status, education, and occupation (Bae, Kang, Chang, Han, & Lee, 2018; Chiu et al, 2013; Li, Chu, & Lai, 2020; Miragoli et al, 2019; Strang, 2020; Papalia et al, 2020; Quayle, 2016; Sprang et al, 2020), as well as depression, pain, resilience, social support, and PTS. The demographic information and characteristics of the participants were entered into the regression model.…”
Section: Methodsmentioning
confidence: 99%
“…The sexual abuse of female children is reported to occur approximately 10% more frequently than that of male children, and 12.6% more frequently in female adults than in male adults (Chiu et al, 2013). Importantly, victims of child sexual abuse experience significantly higher rates of revictimization than those who have not experienced sexual abuse (Papalia, Mann, & Ogloff, 2020). This emphasizes the importance of considering revictimization cases in addition to childhood and adulthood cases.…”
Section: Introductionmentioning
confidence: 99%